Ectopic pancreatic tissue in stomach: A case report. (July 2022) - Paramythiotis, Daniel; Kollatou, Angeliki Sevasti; Simou, Theodora; Karlafti, Eleni; Abba Deka, Ioanna; Petrakis, Georgios; Didangelos, Triantafyllos; Michalopoulos, Antonios
Abstract: Introduction and importance: Ectopic Pancreas (EP) is a rare condition that is mostly found in the Gastrointestinal tract and especially in the stomach. Although the lesion is mainly asymptomatic, non-specific symptoms can be present, making the diagnosis even more challenging. Case presentation: In our case a 52-year-old woman, with heartburn as the only symptom, was undergone successive examinations, indicating a subepithelial lesion in the antrum of the stomach, from which only Magnetic Resonance Imaging (MRI) indicated the presence of ectopic pancreas, while Computed Tomography results considered the mass as Gastrointestinal Stromal Tumor. Wedge gastrectomy was performed in order to extract the lesion and the histopathological examination confirmed the findings of the MRI. The patient fully recovered with no complications. Clinical discussion: In most cases, EP is described in endoscopy as a subepithelial mass with normal mucosa. As EP can mimic other subepithelial masses, even adenocarcinoma, it is of utmost importance not to omit the performance of surgical removal and histopathological examination. Consequently, resection is essential not only for the diagnosis but also for the treatment of the patient. Conclusion: EP is not a usually detected clinical pathology. There is no specific algorithm, which physicians should follow in order to reach the diagnosis without the surgical intervention. For this reason, clinicians should be conscious of the existence of EP in the stomach. Highlights: Ectopic pancreas (EP) is mostly found in the gastrointestinal tract. EP in stomach first considered as a Gastrointestinal Stromal Tumor (GIST). Resection is essential for the diagnosis and for the treatment of the patient.